A preliminary study understanding the possibility and benefits of solar photovoltaic collector integration with vertical green balconies in building facade reconstruction - Wu, Zhang; Chul-Soo, Kim (Frontiers in Energy Research, 2023)
The facades of buildings provide significant potential for photovoltaic panels integration, allowing renewable energy deployment within the built environment. In literature, various options, such as building-integrated photovoltaics, building-integrated photovoltaics-thermal collectors, building-attached photovoltaics, and rooftop photovoltaics, have already been explored. However, this study aimed to develop a new solar photovoltaic collectors’ integration with vertical-green balconies in old high-rise buildings considering the façade reconstruction concepts mainly focusing on the water heating application. The objective of this study is to conduct a preliminary research study investigating such integration possibilities with old buildings considering the façade reconstruction concepts, followed by exploring various benefits. For this, an old high-rise building was rebuilt scientifically and rationally. PHOENICS tool was used to gauge and assess the building’s wind environment first, followed by the solar photovoltaic collector-based facade installation and preliminary assessment. The results include the system design, economic analysis of the solar photovoltaic collector’s application for water heating, calculation of the energy-saving rate, and functional analysis of the solar photovoltaic collectors combined with a vertical green balcony. The outcome of this study suggested that the process-specific rationalization plan can be applied in future urban architecture renovation.